Federmesserkulturen i Danmark – Belyst med udgangspunkt i en amatørarkæologs flintsamling - Riede, Felix; Laursen, Steffen Terp; Hertz, Ejvind (Kuml, 2011)
The Federmesser culture in Denmark in light of an amateur archaeologist’s flint collection In 2010, the dedicated amateur archaeologist Ingvor Filtenborg passed away. For more than 30 years he had systematically walked the fields near his home just to the east of Store Andst near Kolding, Southern Jutland. As this area lies on the current administrative boundary between the museums in Kolding and Sønderskov, his collection became divided. This meant that the culture-historical significance of some aspects of this material has not previously been fully appreciated. This article presents and describes flint tools from his collection that are diagnostic of the so-called Federmesser culture (arch- or curved-backed point groups) dating to the Allerød warm phase of the Late Glacial (12000-11000 years BC). This was a time during which Southern Scandinavia saw dramatic changes in the composition of the local fauna and flora (fig. 2). The diagnostic flint tools from this techno-complex are slender arch-backed points, small flake-scrapers and blade-scrapers with invasive lateral retouch, often forming a tang (so-called Wehlen scrapers). Sites of the Federmesser culture are rare in Denmark and their relationship to the older Hamburgian culture and, in particular, the slightly later Bromme culture remains uncertain. There are methodological challenges associated with surface-collected flint, which clearly limit the analytical potential of such material. The Filtenborg collection is no exception in this regard. However, recent research conducted in other parts of Northern Europe is drawn upon here in order to argue for the likely coherence of the Late Glacial elements in the Filtenborg collection. Importantly, the tools usually seen as diagnostic of the Bromme culture – the large tanged ‘Bromme’ or ‘Lyngby’ points – are found together with the above-mentioned arch-back points in Ingvor Filtenborg’s collection. However, rather than seeing the material as being derived from repeated occupation episodes by people of two separate cultures (the Federmesser culture and Bromme culture, respectively), It is argued that the finds presented here form a single assemblage, and that the inventory actually fits neatly into the artefact spectrum known from many other sites of the Federmesser culture. On the basis of radiocarbon dates and the topographic position of these localities, an attempt is made to place them in their culture-historical and landscape contexts. Material from eight separately recorded localities is presented (site numbers HBV 185, HBV 187, HBV 189, HBV 191, MKH 411, MKH 1111, MKH 1124, and MKH 1116). These cluster around the hilly area to the north of Lake Dollerup and stretch towards the now largely drained wetlands by the village of Gamst (fig. 1). It is likely that material from the immediately adjacent localities HBV 185 and 189, as well as material from HBV 191, MKH 411, MKH 1111, and MKH 1116, should be seen as belonging to only two rather than six different sites. The assemblages contain classic components of the Federmesser culture flint repertoire such as arch-backed points, large tanged points, small thumbnail scrapers and tanged Wehlen scrapers as well as simple scrapers on blades and flakes (Table 1 and figs. 3-6). Furthermore, previous work conducted near the village of Gamst also produced Late Glacial flints, including large tanged and arch-backed points, as well as scrapers (fig. 7). Widening the geographic perspective, this particular combination of tool types also occurs at many localities of the Federmesser culture outside Denmark. The majority of the sites at which the slender arch-backed points occur together with the bulkier large tanged points extend along the periphery of Late Glacial human settlement, from England in the west to Poland and possibly as far as Lithuania, the Ukraine and Belarus in the east (Table 2). It is likely that such a co-occurrence reflects the parallel use of two distinct hunting weapons, the bow and arrow (tipped with arch-backed points) and the dart and spear thrower (tipped with large tanged points). Interestingly, a small but steadily increasing number of these localities has been dated by radiometric methods (see Table 3). Calibration of these dates, together with the dates available for the Bromme culture, shows that the Federmesser culture precedes the Bromme culture in Southern Scandinavia, and that the transition from Federmesser culture to Bromme culture happened some time around 10900 cal BC (fig. 8). What remains unclear is why and how this transition happened and why arch-backed points together with a range of other characteristic tools, seemingly disappeared from the toolkit of the Bromme culture. As Ingvor Filtenborg labelled most of his collection and produced maps of where particular parts of it came from, it was also possible to investigate the position of the localities presented here within their local and regional landscape context. Several other Late Glacial localities are known from the area around Lake Dollerup, such as Hjarup Mose to the south and Estrup Mose and Gamst immediately to the east, and all these sites have yielded very similar flint assemblages. The densest find concentration, however, is found around the lakes near Jels, about 15 km to the south of Lake Dollerup. There too, arch-backed points occur together with large tanged points. Taking an off-site and landscape-focused perspective, these localities can be interpreted as having been part of a diffuse and taphonomically filtered form of settlement hierarchy. Within this, sites such as Jels with relatively high find densities, represent the upper ranks, while the localities around Lake Dollerup represent lower levels of settlement activity (fig. 9). Interestingly, it appears that at Lake Dollerup and elsewhere during the Allerød particular landscape types were preferentially targeted for settlement: undulating terrain with dry, sandy soils in the vicinity of, but rarely directly by, bodies of freshwater. Past decision making about where to rest and settle in the Allerød, it is argued, was contingent on the combined presence of these attributes as well as, perhaps, on a settlement legacy created by previous visits. Late Glacial settlement was thus channelled by particular landscape configurations such as the undulating and topographically complex terrain of the Jutland Ridge. The Late Glacial flint scatters around Lake Dollerup likely constituted ‘significant localities’ repeatedly visited by small groups of pioneering hunter-gatherers. In addition, they were also part of a ‘significant landscape’ stretching from Northern Germany to Lake Dollerup, and beyond to the north and east. Ethnographic observations suggest that such significant landscapes were imbued not only with economic significance, but that they also became integral parts of the social fabric through stories, legends and named topographic features. Over 30 years of fastidious field recognisance by the late Ingvor Filtenborg has produced an interesting collection of Late Glacial flint material, including tools of the elusive Federmesser culture. These flints derive from more or less disturbed surface scatters, but nonetheless hold some analytical value, at least within an off-site context. The co-occurrence of arch-backed points usually associated with the Federmesser culture and large tanged points usually associated with the Bromme culture throws into sharp relief the fact that such typological automatism has so far prevented us from recognising the culture-historical importance of this kind of locality: The presence of large tanged points together with arch-backed points appears to assign such inventories to the earlier part of the Allerød warm phase. If large tanged points are accepted as an integral part of the flint inventory of the Federmesser culture, then many of the single finds of such tools from around Denmark may say more about the settlement patterns of the that techno-complex, rather than the Bromme culture, with which they are usually linked. Other collectors, archaeologists and museums are therefore urged to come forth with similar flint material, so that the actual extent and nature of Federmesser culture occupation in Denmark can be investigated in more detail. Felix Riede Afdeling for Forhistorisk Arkæologi Aarhus Universitet Steffen Terp Laursen Moesgård Museum Ejvind Hertz Skanderborg Museum